Penguatan Kepemimpinan Visioner Dan Pengembangan Kepribadian Dalam Upaya Peningkatan Kreativitas Guru - Adawiah, Siti Asiah; Suharyati, Henny (JURNAL MANAJEMEN PENDIDIKAN, 2024)
STRENGTHENING  VISIONARY  LEADERSHIP  AND  PERSONALITY  DEVELOPMENT  IN  AN  EFFORTS TO INCREASE TEACHER CREATIVITYTeachers are one of the components of education that aims to achieve the ten profiles of Indonesian humans by the law. However, teachers' creativity in permanent private high school foundation teachers an Accredited ”A”   in Bekasi regency is still not optimal. Therefore, this research analyzes the relationship between visionary leadership personality development and teacher creativity. The method used in this research is a survey method with a correlation approach. This research was conducted at 18 private Islamic high schools accredited "A" in the Bekasi Regency area. The instrument used was a questionnaire in the form of a questionnaire indicated to 176 permanent foundation teachers.  The analysis technique used simple correlation and multiple correlation.  The study's results stated the following conclusions:  (1)  There was a positive relationship between visioner leadership and teacher creativity with a correlation coefficient ry.1=0.416 and a functional relationship equation Ŷ= 78.781+0.412X1. Visionary leadership contributes 36.49% of teacher creativity. This means that visionary leadership contributes to teacher creativity. (2) There was a positive relationship between personality and teacher creativity with a correlation coefficient ry.2=0.437 and a functional relationship equation Ŷ = 84,864 + 0,351 X2.   Visionary leadership contributes 36.49% of teacher creativity. This means that personality contributes to teacher creativity. (3) There was a positive relationship between visionary leadership and personality and teacher creativity with a correlation coefficient R= 0.510 and a functional relationship equation Ŷ =  59.684 + 0.285 X1 + 0.259 X2. The contribution of visionary leadership and personality and teacher creativity implied that the teacher's creativity would be progressively better than visionary leadership and personality. The contribution of visionary leadership and personality to teacher creativity was 26,1%. Thus it can be concluded that teacher creativity can be increased through visionary leadership and individual personality.